The effects of feeder space and adjustment on growth performance of finishing pigs - Myers, A.J.; Bergstrom, J.R.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 288 pigs (PIC TR4 × 1050, initially 82 lb) were used in a 91-d study to evaluate the effects of feeder trough space (1.75 vs. 3.5 in/pig) and minimum feeder-gap opening of 0.5 in. (narrow), vs. 1.0 in. (wide) on finisher pig performance. Our hypothesis was that at minimal feeder trough space (1.75 in./pig), feeders should be set at a wide gap opening to avoid limiting feed intake and ADG. The feeders were adjusted to the minimum gap setting, but the agitation plate could be moved upward to a maximum gap opening of 0.75 in. or 1.25 in., respectively. The treatments were arranged in a 2 × 2 factorial with 6 replications per treatment. All pens had the same feeder with 2, 14-in.-wide by 4.5-in.-deep feeder holes. Feeder trough space was adjusted by placing 8 or 16 pigs per pen. Gating was adjusted to give each pig 8 ft2 of floor space. Pigs had ad libitum access to feed and water. All pigs were fed a corn-soybean meal-based diet containing 20% dried distillers grains with solubles (DDGS) in 4 phases. Pen weights and feed disappearance were measured every 2 wk. Narrow-adjusted feeders averaged approximately 48% coverage, and wide-adjusted feeders averaged approximately 85% coverage. Overall (d 0 to 91) there were no trough space × feeder adjustment interactions observed (P > 0.10). However, there was a tendency (P = 0.08) for increased ADG as feeder trough space increased from 1.75 to 3.5 in./pig. Pigs fed with the wide feeder-gap setting had increased (P < 0.01) feed disappearance and poorer (P < 0.01) F/G compared to pigs with the narrow feeder-gap setting. These results suggest that, regardless of feeder trough space, pigs with the wide feeder adjustment appeared to waste more feed, as evidenced by the poorer F/G.
Keywords: Swine; Feeder adjustment; Finishing pig; Trough space